The socially networked classroom: Teaching in the new media age - Kist, William (Corwin, 2010)
'A veritable smorgasbord of ideas and suggestions. This text grabbed me right away, and I started flagging all sorts of ideas even in the earliest chapters. It is as if Bill Kist met me in the hallway, took me by the hand, and simply said, 'Come here, I want to show you something' - Sheila M. Gragg, Technology Integration Coach Ashbury College, Canada 'I loved this book. I learned a great deal about 'texts' and about how to teach 'texts' to students in the digital age. But what was so compelling about this book was the genuineness of the author; he cares passionately about his students and passionately about the subject matter. As Dewey points out, effective education must have an emotional component; indeed, the book's credibility and authority derives from its core emotional energy' - Elliot Soloway, Arthur F. Thurnau Professor University of Michigan, Ann Arbor 'This book is totally compelling and geared to a slice of the teaching profession that is in desperate need of the kind of guidance and insight that Kist offers. By sharing his creative teaching methods, he points out the openings in teachers' practice where shift can happen' - Sue Collins, Integration Technology Specialist, Bedford Public Schools, MA Secondary school students are increasingly plugged in to social networking sites outside of school, but inside the classroom such functions of the web are often ignored. In The Socially Networked Classroom: Teaching in the New Media Age, William Kist identifies and documents the processes of teaching and learning via social networking in the new-media classroom. This book broadens the debate around what constitutes literacy as it tackles practical tasks for educators that include: - Documenting the assignments, assessments, and outcomes of instruction in networked classrooms - Categorizing the classrooms into levels of Web 2.0 applications - Illustrating how the new assignments can be used to address classic classroom questions